Керамічна тара з пізньоскіфських пам’яток Нижнього Дніпра - Абікулова, М.І. (Археологія, 1994)
У публікації проаналізовано керамічну тару, знайдену на 15 пізньоскіфських пам’ятках, що дозволяє накреслити два хронологічних періоди надходження продукції з античних центрів. Типологический анализ керамической тары, найденной на 15 позднескифских памятниках Нижнего Днепра, позволяет наметить два хронологических периода поступления продукции из античных центров; I в. до н. э.— II в. н. э. датируются амфоры, изготовленные в мастерских Южного Причерноморья и, возможно, Средиземноморья, а со II в. н. э. появляются новые типы амфор, часть которых могла быть изготовлена в Ольвии. The topological analysis of ceramic package found in 15 late Scythian relics of the Lower Dnieper permits outlining two chronological periods of delivery of products from antique centers; amphoras produced in workshops of the South Black Sea areas and, probably, in those of the mediterranean Sea areas are dated from the 1st cent. B.C. and 2nd cent. A.D; from the 2nd cent. AD. new types of amphoras appear, some of them being made, probably, in Olbia.